Factors affecting the measurement accuracy of ITER neutron activation system. (7th August 2017) - Cheon, M.S.; Ahn, Y.H.; Pak, S.; Seon, C.; Krasilnikov, V.; Bertalot, L.
Abstract: One of the main purposes of the ITER 2 neutron activation system (NAS) is to evaluate the total neutron production rate from all over the plasma. The measurement accuracy depends on the position and profile of the plasma and the material in front of the irradiation end. It is required to minimize the amount of material and its density variation across the field of view between the plasma and the irradiation end. Due to the radiation and thermal environment of the ITER in-vessel, however, the measurement from ITER NAS cannot avoid the strong influence from in-vessel materials such as the diagnostic first wall, blanket modules, and divertor cassettes, those are located near the irradiation ends. In order to improve the reliability of the measurement in such environment, special cutouts in the diagnostic first wall are introduced near the irradiation end structures located in the port plugs. The effect of the materials and the position and profile of the neutron source in the plasma are evaluated for these irradiation locations, as well as the ones under the divertor cassettes and between blanket modules, by the neutron transport calculation. Calculation results show that simultaneous measurements at upper port and divertor location can provide highly accurate results even without a position or profile correction from other diagnostics.